Loss of Nek11 Prevents G2/M Arrest and Promotes Cell Death in HCT116 Colorectal Cancer Cells Exposed to Therapeutic DNA Damaging Agents. - Sarah R Sabir; Navdeep K Sahota; George D D Jones; Andrew M Fry (PLoS ONE)
The Nek11 kinase is a potential mediator of the DNA damage response whose expression is upregulated in early stage colorectal cancers (CRCs). Here, using RNAi-mediated depletion, we examined the role of Nek11 in HCT116 WT and p53-null CRC cells exposed to ionizing radiation (IR) or the chemotherapeutic drug, irinotecan. We demonstrate that depletion of Nek11 prevents the G2/M arrest induced by these genotoxic agents and promotes p53-dependent apoptosis both in the presence and absence of DNA damage. Interestingly, Nek11 depletion also led to long-term loss of cell viability that was independent of p53 and exacerbated following IR exposure. CRC cells express four splice variants of Nek11 (L/S/C/D). These are predominantly cytoplasmic, but undergo nucleocytoplasmic shuttling mediated through adjacent nuclear import and export signals in the C-terminal non-catalytic domain. In HCT116 cells, Nek11S in particular has an important role in the DNA damage response. These data provide strong evidence that Nek11 contributes to the response of CRC cells to genotoxic agents and is essential for survival either with or without exposure to DNA damage.